A note on estimating minimal changeover time - Dror Hermel; Oded Medina; Nir Shvalb (Cogent Engineering, 2017)
We propose a novel approach for the estimation of change-over times in a continuous production environment, and discuss the importance and prospects of our suggested framework through an illustrative example.